Estudo da microestrutura e resistência à corrosão de ligas binárias Ni-Nb solidificadas rapidamente - Martinez Orozco, Katherine Judith (Universidade Federal de São Carlos, 2018)
The The aim of this work is to study the microstructure and corrosion resistance of rapidly solidified binary Ni-xNb alloys (x= 10, 20, 30, 40, 45, 52 e 57 wt%), additionally the microstructure of the Ni-52Nb alloy, prepared through gas atomization forming process. High-purity elements (99,9 wt% Nb and 99,9 wt% Ni) were used for the pre-alloyed ingots prepared in copper mold by arc melting furnace, and commercial quality materials for the Ni-52Nb alloy by gas atomization process, this alloy was selected owing to their glass forming ability. These Ni-Nb alloys could be employed as coating, deposited by means of remelting laser processes, such as laser cladding. Besides, there is little evidence in literature about their microstructural morphology. Characterization was performed through: Microhardness Vickers test, Potenciodynamic Polarization, X-Ray Diffraction (XRD), Optical Microscopy (OM), Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) together with Energy-Dispersive X-Ray Spectroscopy (EDS), Focused Ion Beam (FIB). Differential Scanning Calorimetry (DSC) was performed for the Ni-20Nb sample in order to confirm the formation Ni8Nb metastable phase. An increase in hardness values were observed with the increasing of Nb content (between 70 HV and 860 HV). Potenciodynamic Polarization curves showed an important increase in passivation values of the alloys with as function of Nb content, improving significantly the pitting corrosion resistance when compare with commercial superalloys as Inconel 625. Alloys solidified in arc melting furnace showed marked variation in their microstructure as function of Nb content. The metastable phase Ni8Nb was identified as showing needle-like morphology, which is not reported in literature appearing in Ni-Nb binary alloys, secondary phases Ni3Nb and Ni6Nb7 were also observed. Atomized powder of Ni-52Nb alloy obtained was sieved in different sizes (between 45 and 250 μm), and amorphization was observed to occurred along the all range of sizes.
Study of microstructure and corrosion resistance in binary alloys Ni-Nb rapidly solidified
Keywords: Ligas Binárias; Nióbio; Solidificação Rápida; Passivação; Binary alloys; Niobium; Rapid solidification; Passivation; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO